1967
DOI: 10.1007/bf02635616
|View full text |Cite
|
Sign up to set email alerts
|

A double label radiotracer approach to detergency studies

Abstract: The comparative detergency of a series of built detergents of commercial interest has been measured via the use of a doubly labeled multicomponent synthetic soil. Four test fabrics: cotton, nylon, Dacron, and Dacron/cotton were soiled with the seven-component soil, which was in turn almost completely and then individually labeled. The fabrics were washed in a conventional Tergotometer under cold-water and hotwater conditions. Analyses of the fabrics before and after washing were made by liquid scintillation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…These polar components were much more easily removed from the cotton and polyester fabrics than was the nonpolar triolein, agreeing with previous research [3,4,9,13,16,17]. The removal of both polar and nonpolar components was similar for the acrylic and nylon fabrics.…”
Section: Response Surfacessupporting
confidence: 90%
See 2 more Smart Citations
“…These polar components were much more easily removed from the cotton and polyester fabrics than was the nonpolar triolein, agreeing with previous research [3,4,9,13,16,17]. The removal of both polar and nonpolar components was similar for the acrylic and nylon fabrics.…”
Section: Response Surfacessupporting
confidence: 90%
“…The inverse relationship between wash temperature and removal of the nonpolar triolein from polyester is visible in the response surface plots. This relationship has been previously noted [3,4,9]. Fort et al [3] found evidence of slight diffusion of tristearin into polyester films at high temperatures; however, Obendorf el at.…”
Section: Response Surfacesmentioning
confidence: 64%
See 1 more Smart Citation
“…Soap formation due to the presence of fatty acids aids removal of other oily soils as well. Several studies (1,39,41,42) have reported that residual oily soil contains a greater percentage of nonpolar components than fresh oily soil. Polar soils tend to be more easily removed in aqueous detergent systems.…”
Section: Selective Removal Of Oily Soils Upon Washingmentioning
confidence: 98%
“…In contrast to fatty acids, triglycerides are generally difficult to remove by laundering (35)(36)(37)(38)(39). Retention of triglycerides becomes more severe with successive soilings and washing.…”
Section: Selective Removal Of Oily Soils Upon Washingmentioning
confidence: 99%